Pembuatan Otomatisasi Alat Pengecekan pH Air Pada Mesin Pemberi Pakan Ternak Ikan - Dongoran, Rahmat Sati; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2023)
An automatic fish feeding and water pH control system for catfish farming is being developed. The system involves assembling and constructing a control circuit with electronic components and sensors, applying IoT technology to control the pH regulator remotely. The device is designed to control water pH through circulation and periodic measurement of water pH in the catfish pond using a pH sensor (PH4502C type). The system utilizes a digital RTC DS1307 module to schedule feeding times. Communication between a smartphone and the control circuit occurs over the internet for data transfer and commands. It enables feeding control for catfish ponds and integrates with smartphones. The machine designed for feeding and water pH regulation in fish farming uses an Arduino device with Node MCU as the control unit. The pH sensor and water pH regulator functions are implemented to control and check water acidity in the pond. Automation processes include using a servo motor for automatic feeding, a pH sensor for water pH measurement, and a water pump for pH regulation. The RTC serves as a digital clock to provide timing information to the microcontroller, ensuring the programmed tasks run as scheduled. The IoT system allows remote control and monitoring, enabling bidirectional communication using a WiFi adapter device, specifically the Node MCU. The Node MCU connects to a WiFi hotspot and interfaces with the Blynk server on the smartphone. The system's menu includes pH display, buttons to activate/deactivate the water pump, feeding control, and notifications.